The Effect of Perceived Benefits, Perceived Convenience, and Perceived Security On Decision To Use QRIS - Ningrum, Amalia Septia; Parmariza, Yennida (Journal of Fundamental Management (JFM), 2026)
This study aims to examine and analyze the influence of Perceived Benefits, Perceived Ease, and Perceived Security on the decision to use QUICK RESPONSE CODE INDONESIA (QRIS). The population in this study consists of students at Mercu Buana University Meruya who use QRIS. The sampling method employed convenience sampling using non-probability sampling, with a sample size of 120 respondents. This is a quantitative study using a survey method for data collection, with the research instrument being a questionnaire using an ordinal scale as the research tool, and data analysis was conducted using Partial Least Squares. The results of the study prove that Perceived Benefits, Perceived Ease, and Perceived Security have a positive and significant influence on the decision to use QRIS.